Anticipation and harvest delay in oil and protein contents of soybean seeds, grow crops Valiosa RR - Luis Finoto, Everton (2017)
The objective of this work was to evaluate the physiological quality and oil and protein content of soybean seeds harvested in different stages of plant development and different periods of harvest delay. The cultivar studied was BRS Valiosa RR and the experimental design was of randomized blocks with three replications. Eleven treatments were established, constituting different times of harvest in the following stages: R5,1, R5,3, R5,5, R6, R7,1, R7,3, R8,1, R9, R9+10days, R9+20 days and R9+30 days. The anticipation of the harvest was made possible through the application in predetermined stages, of herbicide Diquat (400 g ha-1) with manual coastal spray with nozzle "type fan" set to volume of 300 L ha-1. After the harvest it was done the evaluation of physiological quality of seeds and the determination of the levels of oil and protein. It was noted that the stadium R7.1 was the harvest season that showed the highest percentage in the germination test, demonstrating that the anticipation of the harvest did not caused significant loss in seed vigor. At the grain filling stage, oil levels were lower and protein larger. Both stabilized from R7.1 to the R9 stadium and showed downward trend with the harvest delay.